Evaluating the ability of goalkeepers in English Premier League football - Gelade, G. (Journal of Quantitative Analysis in Sports, 2014)
This paper examines the performance of goalkeepers in the English Premier League. A commonly used metric to assess goalkeeper ability is the saves-to-shots ratio. It is shown that goalkeepers playing in weak teams have to defend against on-target shots that have a relatively high probability of scoring as compared to their counterparts in higher-performing teams. This tends to produce a downwards bias in the save-to-shots ratio of goalkeepers in weak teams, an effect which may lead to their ability being underestimated. A logistic regression model is used to adjust goalkeepers` saves-to-shots ratios for differences in save difficulty. The adjusted ratio is more stable across seasons, suggesting that it is a more reliable estimate of true goalkeeper ability than the unadjusted ratio.